Double Valve Infective Endocarditis Presenting with Acute Ischemic Stroke - Bahadir Sarli, Mehmet Ugurlu; Oguz Baktir, Ahmet; Erturk, Fazilet Sag (Journal of Cardiovascular Medicine and Cardiology, 2015)
Infective endocarditis is a potentially fatal infectious disease which usually presents with various clinic scenarios. Although the disease generally presents itself with fever, cardiac murmur (bruit), splenomegaly and anemia; in this case we report a double valve endocarditis of a 23 years-old female patient who was admitted to our neurology clinic with acute ischemic stroke.